Attributes of Transport Service in Retail-Industry Relationship - Martins, Ricardo Silveira; Xavier, Wescley Silva (Review of Business Management, 2011)
In distribution segment, logistics activities are more easily perceived as value generating. Among them, the transportation it is highlighted. This study evaluated the shippers’ transportation management in retail service. The motivation of the study is the evidence from the literature that there are differences in management of transport, in terms of attributes of service, according to the client, as well as the format of the demand for transport services and to meet their segments of the supply chains. In the universe of 400 manufacturing companies located in the state of Minas Gerais, 101 were selected as they had a retail account for more than 60% of their sales, which was analyzed as to the desired constructs and attributed evaluation. In general, industrial shippers seem to minimize the importance of logistics in the retail service, giving the transport merely operational functions and not strategic ones. They fail to aggregate the value of logistics to their products and services. The results forwarded to specific management issues relevant such as the relationship between orders fulfillment and problems of internal processes, structure of distribution channels, logistics networks and decisions about to internalizing/outsourcing logistics services. Key words: Service level. Transportation management. Industry-retail relationship.